DA’I SEBAGAI PEWARIS NABI - Malik, Hatta Abdul (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2010)
Da'i are the inheritors of the prophets. The task of the prophets has been described by Allah through the Koran.When the Prophet was dead, then the beneficiary is the clergy. Not all scholars, including the heir to the Prophet. Only scholarswho also assumed the duties of a prophet obligation. Da'i as the spearhead of the spread of Islam need to know the dutiesof the Prophet and also imitate the Prophet in undertaking the God who charged him